Selected Pharmacological Studies Of Cinnamomum Iners Standardized Leaves Methanolic Extract - Mustaffa, Fazlina (2011)
Cinnamomum iners standardized leaves methanolic extract (CSLE) was subjected to phytochemical screening, antioxidant, toxicity studies, analgesic and antimicrobial activity. Phytochemical screening of CSLE showed the presence of cardiac glycoside, flavanoid, polyphenol, saponin, tannin and terpenoid. These secondary metabolites might be contributed to the bioactivity of CSLE. The overall antioxidant research provides information that CSLE showed moderate antioxidant activity. This might be due to the high phenolic content (211.94 ± 13.04 mg GAE/g plant material) in CSLE.